2008
DOI: 10.1007/s10295-008-0438-2
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the design of probiotic products for the prevention of major diseases in dairy cattle

Abstract: Probiotics are frequently used for multiple objectives and the majority of applications are performed both in human beings and in different animals. The specificity of species showed by the members of the indigenous microbiotia led us to isolate lactic acid bacteria (LAB) from their natural bovine ecosystems and to select those with probiotic potentiality. The beneficial probiotic LAB were isolated from the vaginal tract and mammary gland of adult heifers, faeces and oral cavity of newborn calves. Bacterial st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 30 publications
2
37
0
Order By: Relevance
“…In the Mie fecal samples, L. animalis, L. johnsonii, L. reuteri, and L. plantarum were found in all the dairy cows tested; thus, except for L. plantarum, the LAB species usually detectable in the gut were indeed seen in the present study (Krause et al, 2003;Hernandez et al, 2008;Nader-Macías et al, 2008). Lactobacillus acetotolerans, L. suebicus, and L. casei appeared to survive in the Mie dairy cow feces.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…In the Mie fecal samples, L. animalis, L. johnsonii, L. reuteri, and L. plantarum were found in all the dairy cows tested; thus, except for L. plantarum, the LAB species usually detectable in the gut were indeed seen in the present study (Krause et al, 2003;Hernandez et al, 2008;Nader-Macías et al, 2008). Lactobacillus acetotolerans, L. suebicus, and L. casei appeared to survive in the Mie dairy cow feces.…”
Section: Discussionmentioning
confidence: 51%
“…However, as Rodriguez-Palacios et al (2009) acknowledged, the isolation of L. plantarum from the bovine gut is rare. The LAB species usually detected in the gut are Streptococcus bovis, Lactobacillus vitulinus, Lactobacillus ruminis, Lactobacillus johnsonii, and Lactoabacillus murinus (Krause et al, 2003;Hernandez et al, 2008;Nader-Macías et al, 2008). This raises a debate on how to select LAB species for developing probiotic supplements.…”
Section: Introductionmentioning
confidence: 97%
“…However, the use of antibiotics in animal husbandry is in question because of antibiotic resistance of microorganisms. In an effort to replace antibiotics from bovine feeds, many additives have been proposed including the use of probiotics (28, 29). In fact, some few studies have shown that probiotic bacteria can be used as growth promoters in calves instead of antibiotics to counteract the negative effects of their widespread use (30).…”
Section: Probiotics For the Bovine Hostmentioning
confidence: 99%
“…Due to an increased probability of transmission of antibiotic resistance to indigenous and potential pathogens through antibiotic implementation as well as poor cure rates of mastitis during lactation, the conventional treatment methods have to be revisited and innovative and sustainable therapeutics sought (Khachatourians, 1998;Saini et al, 2012). The application of probiotic bacteria, that when administered in appropriate amounts confers a beneficial effect to the host (FAO and WHO, 2006), has been widely studied as a novel approach (Crispie et al, 2004;Galvin et al, 1999;Nader-Macías et al, 2008). These may include the lactic acid bacteria (LAB), which are considered as safe (GRAS, Generally Recognized as Safe) and can be detected on teat epithelia, in bedding material, on plants and in milk (Chaimanee et al, 2009;Espeche et al, 2009).…”
Section: Introductionmentioning
confidence: 99%